The riddle of spiritual pedagogy: how is authoritative spiritual teaching possible? - Dunch, MI (2022)
This thesis asks: can a spiritual teacher be said to teach with authority, as much of the Christian tradition holds and, indeed, requires to continue itself? To answer this question, a secondary question is pursued: what is the relationship of spiritual authority to other types of authoritative teaching? The spiritual pedagogue attempts to form others to live according to God’s will, which is mysterious in principle. Unlike most other disciplines, the spiritual teacher cannot claim authoritative knowledge of the essence of her discipline. Nevertheless, I argue that spiritual teaching authority is a legitimate though limited form of authority, and that a sign of such authority is a self-consciousness of its own limitations.